THE EFFECT OF CORPORATE SOCIAL RESPONSIBILITY (CSR) ON IMAGE PT TERMINAL TELUK LAMONG (STUDY ON THE UMKM KANTIN AND UMKM CORNER) - Mardiana, Irndika Pramestya; Setiadi, Tatak (The Commercium, 2024)
The company's image is formed by various activities carried out by the company, such as corporate social responsibility. The efforts made by PT Terminal Teluk Lamong to build a positive image include implementing Corporate Social Responsibility (CSR). This study aims to determine the influence of CSR on the image of PT Terminal Teluk Lamong. The research adopts an explanatory method with a quantitative approach. The results of the correlation coefficient test show a value of 0.597, indicating a significant influence of CSR on the image of PT Terminal Teluk Lamong, which is considered quite strong. The coefficient of determination test results show that 35.6% is influenced by CSR, while the remaining 64.5% is influenced by other factors not explained in this regression model. Through the CSR programs for UMKM Canteens and UMKM corners, PT Terminal Teluk Lamong demonstrates its commitment to contributing to the improvement of the local community's economic well-being. As a result, the company has successfully built a positive image as an agent of change that cares about and effectively contributes to economic growth.